Effect of extrusion process parameters and pregelatinized rice flour on physicochemical properties of ready-to-eat expanded snacks - Gat, Yogesh (J Food Sci Technol, 2014)
Present study was conducted to investigate effects of pregelatinized rice flour and extrusion process parameters such as feed moisture (16–19 %), die temperature (115–145 °C) and screw speed (150–250 rpm) on physicochemical properties of ready-to-eat expanded snacks by using co-rotating twin-screw extruder. Higher die temperature increased extrudate density and WSI but reduced die pressure, torque and expansion. Increased feed moisture content resulted in extrudates with increased density, WAI and hardness but reduced die pressure, expansion and WSI. Screw speed was found to have no significant effect on expansion and hardness of extrudates, while increase in screw speed resulted in increased WAI of extrudates and reduced torque of extrudates. Effect of pregelatinized rice flour on extrudate expansion and hardness was analysed at 16 % feed moisture, 135 °C die temperature and 150 rpm screw speed. Use of pregelatinized rice flour increased expansion while it reduced hardness of extrudates.